Boundary extension effect remembering different content pictures - Radzevičienė, Aldona; Jankūnaitė, Jurgita (Psichologija, 2020)
The goal of this study was to investigate in which cases boundary extension occurs when repainting visual images with different content from your memory. The method that was used in this study is based on a meta-analysis conducted by Hubbard et al. (2010). The method consists of 12 stimuli (dimensions 10x15 cm), which show a photographic image or sketch of a painting. Presented stimuli contain images with different content – finished object, object with its corners removed, emotionally neutral, positive and negative object, moving object; 120 respondents participated in the study, their age ranged from 14 to 45 years old (average age – 25,6).The first hypothesis, stating that boundary extension is more frequent with images of objects with removed corners than those of finished objects repainted from memory, was confirmed. The second hypothesis, stating that boundary extension is more frequent with images of emotionally neutral objects than those of emotionally positive or intense objects repainted from memory, was confirmed. The third hypothesis, stating that boundary extension while repainting images that contain containing moving objects, form memory, unfolds from the expected direction of object movement – the left side, was not confirmed. It was found that boundary extension unfolded at the top of a painting (bird) and at the bottom of a painting (vehicle). The fourth hypothesis was partly confirmed – that boundary extension while repainting images from memory with different content stimuli is more likely to happen among teenagers (years 14–19). The central tendency is more likely among younger adults (20–30), and boundary restriction – among older adults (31–45). The fifth hypothesis was confirmed. As expected, boundary extension when repainting images of different content from memory more often occurrs with women than men. The sixth hypothesis, stating that boundary extensions are more often when repainting images from memory that were painted and are not photographical images, was not confirmed.
Keywords: Boundary extension; Boundary restriction; Visual Memory; Picture perception